Исследование параметров облачности и явлений по данным спутникового и радиолокационного зондирования (Географический вестник=Geographical bulletin, 2017)
Разработана методика определения метеорологических параметров с использованием дистанционных систем зондирования атмосферы. По спутниковой информации восстановлены параметры облачности (границы, площади, объемы), интенсивность осадков, водность, водозапас облаков, опасные явления и исследованы их изменения во времени и пространстве. Проанализированы методы комплексного анализа исследуемых параметров.RESEARCH OF PARAMETERS OF OVERCAST AND THE PHENOMENA ACCORDING TO SATELLITE AND RADAR-TRACKING SOUNDING The technique of definition of meteorological parameters with use of remote systems of sounding of atmosphere is developed. Under the satellite information overcast parameters (borders, the areas, volumes), intensity of deposits, liquid water content, a water stock of the clouds, the dangerous phenomena are restored and their changes in time and space are investigated. Methods of the complex analysis of investigated parameters are analysed.